Frequency of Union in Intramedullary Solid Nailing (SIGN nailing) Via Open Reduction for the Treatment of Fracture Shaft of Tibia - TAYYAB HASSAN, SYED MUHAMMAD (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Fractures involving the shaft of long bones are common worldwide and tibial fractures are among the most common lower limb injuries to be treated by an orthopedic surgeon. Objective: The objective of this study was to find frequency of union in intramedullary solid nailing (SIGN nailing) via open reduction for the treatment of fracture shaft of tibia. Study Design: This Randomized controlled trial was conducted in Department of Orthopedic Surgery, Allied Hospital, Faisalabad from July 1st 2014 to December 31st 2014. After taking approval from hospital ethical committee, patients coming through emergency fulfilling the inclusion criteria were enrolled and informed consent was taken. After initial treatment following ATLS protocol, x-ray was taken from hospital radiology department and then patients were treated with intramedullary nailing. Both the procedures were performed by consultant orthopedic surgeon. Union of bone was assessed on x-ray (as in operational definition) at 6th month. Results: A total of 130 cases fulfilling the inclusion/exclusion criteria were enrolled to compare the frequency of union in intramedullary solid nailing (SIGN nailing) via open reduction for the treatment of fracture shaft of tibia. Mean age of the patients was calculated as 35.38+12.49 years. Frequency of union in intramedullary solid nailing (SIGN nailing) via open reduction for the treatment of fracture shaft of tibia was done which shows union in 78.46%. P value was calculated as 0.05 which shows a significant difference. Conclusion: It is concluded that that the frequency of union was significantly lower in intramedullary solid nailing (SIGN nailing) for the treatment of fracture shaft of tibia as compared to cannulated nailing.